Fabrications and applications of low cost ceramic membrane from kaolin: a comprehensive review - Hubadillah, Siti Khadijah; Othman, Mohd Hafiz Dzarfan; Matsuuraa, Takeshi; Ismail, A.F.; A. Rahman, Mukhlis; Harun, Zawati; Jaafar, Juhana; Nomur, Mikihiro (ScienceDirect, 2018)
The application of low cost ceramic membrane from kaolin has attracted much interest due to its excellent mechanical stability, chemical and thermal resistivity and most importantly, because it is cost effective, in some cases, compared to polymeric membranes. The advantage of kaolin based ceramic membrane is its thermal properties that allow sintering at much lower temperature than alumina. Although many studies have been made on the application of kaolin based ceramic membranes, detailed discussions were scarcely made and the information on the fabrication of ceramic membrane from kaolin is very limited. This article is aimed to make a comprehensive review on ceramic membrane from kaolin for its fabrication methods and applications. An attempt is also made to show the future direction of the R and D on the kaolin based ceramic membrane.